2011
DOI: 10.1007/s10765-011-1051-6
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Tungsten–Rhenium Thermocouples in the Range from 0 °C to 1500 °C

Abstract: The effect of exposure up to 1500 • C on emf values of type C (95 % tungsten 5 % rhenium vs. 74 % tungsten 26 % rhenium) thermocouples were evaluated. Three thermocouples consisting of thermocouple wires of 0.5 mm diameter, twin-bore beryllia tubes, and tantalum sheaths were prepared. After three type C thermocouples were calibrated in the range from 0 • C to 1550 • C, which confirmed insignificant difference among them, the drifts of two among them were measured at the palladium-carbon (Pd-C) eutectic point (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Maximum offsets for both type are quite similar in magnitude, 4.8 C for Type A and -4 C for Type C. Ulanovskiy et al [5] reported that Type A thermocouples, when tested above 1350 C, generate larger EMF than is specified by the standard. Ogura [6] found similar behavior to that shown in figure 4 when they conducted aging at 1500 C. That is, the EMF of the Type C thermocouple initially increased and after 20 hours it began decreasing. At 100 hours of exposure time, the EMF was less than its initial value by more than 1 C. It is worth noting that thermocouple A52 exhibits minimal aging effect.…”
Section: Discussion Drift Due To Exposure To High Temperaturesupporting
confidence: 67%
“…Maximum offsets for both type are quite similar in magnitude, 4.8 C for Type A and -4 C for Type C. Ulanovskiy et al [5] reported that Type A thermocouples, when tested above 1350 C, generate larger EMF than is specified by the standard. Ogura [6] found similar behavior to that shown in figure 4 when they conducted aging at 1500 C. That is, the EMF of the Type C thermocouple initially increased and after 20 hours it began decreasing. At 100 hours of exposure time, the EMF was less than its initial value by more than 1 C. It is worth noting that thermocouple A52 exhibits minimal aging effect.…”
Section: Discussion Drift Due To Exposure To High Temperaturesupporting
confidence: 67%
“…Usually, a W-Re thermocouple has a typical uncertainty of 1%, which is 20 °C at 2000 °C [1]. Under real operation, thermal drift of the W-Re thermocouple is always a serious issue, and it becomes increasingly severe as the temperature increases [2]. However, the drift behaviour of thermocouples is difficult to predict, and even thermocouples constructed from the same batch of thermocouple wire exhibit quite different performances.…”
Section: Introductionmentioning
confidence: 99%
“…The lower output of the Land-Jewell thermocouple relative to the type B thermocouple, previously considered a drawback, is mitigated these days by the prevalence of very sensitive digital voltmeters, provided its use is restricted to temperatures in excess of 400 °C. As well as the advantage of its high melting temperature, its high Rh content relative to the letter-designated thermocouples lends it greater stability than the other Pt-Rh thermocouple types above about 1200 °C [2] and, in addition, its performance is far superior to the refractory metal W-Re thermocouples [3][4][5] under a wide range of conditions [6][7][8]. This is because alloys with high Rh content are less sensitive to local changes in Rh content caused by evaporation of the oxides of Pt and Rh which are very volatile at high temperatures [9,10].…”
Section: Introductionmentioning
confidence: 99%